3% diquafosol sodium eye drops in Chinese patients with dry eye: a phase IV study - Wang, Wenying; Sun, Xiaonan; Zhao, Jiangyue; Hao, Jilong; Zhao, Shaozhen; Yan, Xiaoming; Shen, Ye; Jin, Xiuming; Cheng, Yan; Wang, Linnong; Xu, Jianjiang; Zhao, Peiquan; et al. (Frontiers in Medicine, 2023)
To evaluate the efficacy and safety of 3% diquafosol sodium eye drops in Chinese patients with dry eye in the real-world setting, 3099 patients with dry eye symptoms were screened according to Asia Dry Eye Society latest recommendation. Among them, 3000 patients were enrolled for a phase IV study. We followed up with multiple clinical characteristics including corneal fluorescein staining, tear break up time, Schirmer's tests, visual acuity, intraocular pressure, and others. The follow ups were performed at baseline, 2 weeks and 4 weeks after treatment. Based on the results of corneal fluorescein staining and tear break up time, all age and gender subgroups exhibited obvious alleviation of the symptoms among the patients with dry eye, and the data in elderly group showed the most significant alleviation. All the adverse drug reactions (ADRs, 6.17%) were recorded, among which 6% local ocular ADRs were included. Meanwhile, mild ADRs (91.8%) accounted for the most. Most of the ADRs (89.75%) got a quick and full recovery, with an average time at 15.6 days. 1.37% of patients dropped out of the study due to ADRs. In summary, the use of 3% diquafosol sodium eye drop is effective and safe in the treatment of dry eye, with a low incidence of ADRs showing mild symptoms. This trial was registered at Chinese Clinical Trial Registry ID: ChiCTR1900021999 (Registration Date: 19/03/2019)